Histopathologic findings on gestational days of 15-18 in rats with adriamycin induced esophageal atresia [Sicanlarda adriamisin ile olusturulan ozofagus atrezisi modelinde gestasyonun 15-18. gunlerindeki histopatolojik bulgular] - (:unkn) unknown (My University, 2000)
Presentation of adriamycin induced esophageal atresia model in rats is a new beginning for embriyologic investigations of this congenital anomaly. Most of the histopathological studies with this model designed to examine gestational period between 11 to 13th days. The aim of this study is to describe the histopathological features of esophageal atresia on days 15 through 18. Adriamycin (2 mg/kg/dose) was administered intraperitoneally to 19 of 26 time-pregnant Sprague-Dawley rats on gestational days of 8,9, and 10. Normal saline was administered to the remaining seven rats. Horizontal sections of 252 fetuses from both groups were examined histopathologically. Fifty out of 183 (27%) adriamycin-exposed fetuses developed esophageal atresia (EA), and tracheal agenesis (TA) was seen in other two. Histological findings of adriamycin-exposed fetuses without EA or TA were similar with control group fetuses. Differentiation of structures on esophageal and tracheal wall was observed on 17th and 18th gestational days. Distance between trachea and vertebral cartilage in fetuses with EA were comparable with in those without EA. Tracheal structure in EA, and esophageal structure in TA kept their normal histological appearance. Exposure to adriamycin did not altered esophageal histology in fetuses without EA. As our data can be adjusted to different theories, we recommend to investigate the entire gestational period to make more reasonable embriyogenetic explanations.
Keywords: Adriamycin; Atresia; Embryo; Esophagus; Fistula; Rat; Trachea